ПРИМЕНЕНИЕ ПЕРОРАЛЬНЫХ АНТИКОАГУЛЯНТОВ ПРИ ФИБРИЛЛЯЦИИ ПРЕДСЕРДИЙ: СОВРЕМЕННОЕ СОСТОЯНИЕ ПРОБЛЕМЫ И НОВЫЕ ВОЗМОЖНОСТИ - Г. И. Сторожаков; С. Н. Борисов; Г. Е. Гендлин; А. В. Мелехов (Архивъ внутренней медицины, 2013)
Contemporary Russian and international experience of prophylaxis of thromboembolic complications of atrial fibrillation indicates that the most popular strategy for the prevention of stroke with warfarin is far from optimum. Measures proposed to improve it (physicians’ knowledge of pharmacodynamics features, pharmacokinetics and pharmacogenetics of the drug, regular monitoring of International Normalized Ratio) can not always be implemented in clinical practice. Introduction of new anticoagulants, as effective as warfarin, but more convenient to use, is very important now. Such anticoagulant is rivaroxaban (Xarelto). Authors believe that comparable safety with warfarin and not inferior/superior safety, ease of dosing, no need for laboratory monitoring during therapy, no adverse interactions with medications and food products will allow rivaroxaban to increase significantly the compliance of doctors and patients to anticoagulant therapy in the near future.